2004
DOI: 10.1104/pp.103.027045
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Sulfonylurea by AtMRP5, an Arabidopsis Multidrug Resistance-Related Protein That Functions in Salt Tolerance

Abstract: Recently, a new member of the ABC transporter superfamily of Arabidopsis, AtMRP5, was identified and characterized. In the present work, we found that AtMRP5 can bind specifically to sulfonurea when it is expressed in HEK293 cells. We also present evidence for a new role of AtMRP5 in the salt stress response of Arabidopsis. We used reverse genetics to identify an Arabidopsis mutant (atmrp5-2) in which the AtMRP5 gene was disrupted by transferred DNA insertion. In root-bending assays using Murashige and Skoog m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 62 publications
1
43
0
2
Order By: Relevance
“…Geisler et al (2005) used MDR/PGP inhibitors cyclosporin A and verapamil to inhibit the eZux of auxin in PGP 1 transformed yeast. By studying the hypersensitive response of A. thaliana to salt stress, glibenclamide was used to analyze the response of the atmrp5-2 mutant (Lee et al 2004). As shown in Table 2, the secretion of some of the phytochemicals produced by Arabidopsis was inhibited by these compounds, suggesting that a primary transporter might be involved in their exudation into the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Geisler et al (2005) used MDR/PGP inhibitors cyclosporin A and verapamil to inhibit the eZux of auxin in PGP 1 transformed yeast. By studying the hypersensitive response of A. thaliana to salt stress, glibenclamide was used to analyze the response of the atmrp5-2 mutant (Lee et al 2004). As shown in Table 2, the secretion of some of the phytochemicals produced by Arabidopsis was inhibited by these compounds, suggesting that a primary transporter might be involved in their exudation into the medium.…”
Section: Discussionmentioning
confidence: 99%
“…In the microarray analysis, among the 17 genes up-regulated by at least 3-fold by overexpression of MYBS3 as well as by cold in the wild type (Supplemental Fig. S4A), several of them have previously been implicated in stress responses and/or tolerance in plants (Supplemental Table S1), such as Glu decarboxylase, which catalyzes the conversion of Glu to g-aminobutyrate and is activated in response to heat in Arabidopsis roots (Bouche et al, 2004) and to anoxia in rice roots (Aurisano et al, 1995); WRKY77, which activates the ABA-inducible HVA22 promoter in cereal grains (Xie et al, 2005), and several WRKYs have been shown to confer biotic and abiotic stress tolerance in Arabidopsis (Ross et al, 2007;Lai et al, 2008;Zhou et al, 2008); and multidrug resistance protein 4, whose expression is activated by arsenate and arsenite stresses in rice seedlings (Chakrabarty et al, 2009) and whose homologous genes confer salt tolerance (Lee et al, 2004) and oxidative stress tolerance against pathogens (Sun et al, 2006) in various plant species.…”
Section: Mybs3 Suppresses the Dreb1-dependent Pathway Under Prolongedmentioning
confidence: 99%
“…Interestingly, SUR1 (AAC36724) and SUR2A (NP_005682.2) subunits both show a high degree of sequence homology with several members of the multidrug-resistance protein family in Arabidopsis, including the ABC transporters of mitochondrion (AtATM1-3) (32% identity and 53% positivity over 1381 aminoacids (BLASTP algorithm) between SUR1 and AtMRP1). While AtATM1-3 proteins are implicated in iron homeostasis [31], AtMRP5 has been proposed to regulate a potassium channel activity [32]. Thus, one possibility is that an ABC-transporter protein associates with e.g.…”
Section: Discussionmentioning
confidence: 99%